Educator Strategies in Instilling Early Childhood Religious Character - Habibah, Ummu -; Ni’amah, Miftaku; Siyono, Siyono; Mardi, Mardi; Asriadi, Asriadi (Absorbent Mind, 2023)
This study analyzed educators' strategies for instilling early childhood religious character. This research uses a descriptive qualitative method and data collection procedures through interview techniques, observation, and documentation. The collected data related to students' numeracy skills and the use of innovative tree media were analyzed using data reduction, data presentation, and conclusions. The result of this study is that religious character is an integration of creed, sharia, and morals. PAUD Kartika Buana Pagotan Geger Madiun instills religious feelings in students, which is associated with the creation of PAUD religious culture both related to aspects of creed, sharia, and morals as well as the encouragement of leaders to go through the order of spiritual values that are entrenched in PAUD. The creed aspect is introduced through songs, games, and fairy tales. The Sharia aspect invites students to practice worship, and the moral element is instilled through school rules and student promises. The commitment to maintaining religious culture in PAUD Kartika Buana is always considered, even though the facilities for places of worship have yet to be available.